Technological Sovereignty as Ability, Not Autarky - Christoph March; Ina Schieferdecker (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Aspirations towards technological sovereignty increasingly pervade the political debate. Yet, an ambiguous definition leaves the exact goal of those aspirations and the policies to fulfill them unclear. This leaves room for partly particularly negative interpretations, such as equating the concept with a strive for autarky, nationalism, and the roll-back of globalization. We develop a competence-based definition of technological sovereignty, which puts innovation policy at the core of fulfilling sovereignty aspirations. Moreover, we show how our definition realigns technological sovereignty with international cooperation and trade. Two case studies illustrate how innovation policy might be used to achieve technological sovereignty.
Keywords: O32; O33; O38; 330; technological sovereignty; innovation policy; international cooperation; Industrie 4.0; EUV lithography